Antibacterial and Antioxidant Activities of Ginger Essential Oils - Mega Ferdina Warsito; Febriana Untari; Anggia Prasetyoputri; Fauzy Rachman; Eris Septiana; Asep Bayu; Akhirta Atikana; Linda Sukmarini; Masteria Yunovilsa Putra (Indonesian Society for microbiology, 2021)
Ginger is a rhizomatous perennial herb that grows abundantly in tropical areas. It has been used around the world as a spice, flavoring agent, and ingredient in traditional medicine. Ginger essential oils (GEOs) are derivatives of ginger that can be found in various products used in daily life, such as food, pharmaceutical, and cosmetics. The present study analyzed the chemical compositions, antioxidant, and antibacterial activities of three commercially available GEOs. The compositions of GEOs were identified using the gas chromatography method. The antioxidant activity was evaluated using 2,2-diphenyl-1-picryl-hydrazyl (DPPH) and 2,2’-azinobis- (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay methods. The antibacterial activity was determined using a disc diffusion assay based on the diameter of the inhibition zone (DIZ). The main compounds identified from the samples were zingiberene, α-curcumene, β-sesquiphellandrene, camphene, α-farnesene, β-bisabolene, α-pinene, and 3-carene. The IC50 values were found to be 5.3023 and 1.4504 mg/mL for GEO1; 0.9249 and 0.5276 mg/mL for GEO2; and 10.4463 and 3.3535 mg/mL for GEO3 when evaluated using DPPH and ABTS assay methods, respectively. All samples showed antibacterial activity against Staphylococcus aureus ATCC 13420 and Bacillus subtilis (collection of Indonesian Institute of Sciences), while only GEO2 and 3 displayed inhibitory effect against Escherichia coli ATCC 9637.